Analisis Keandalan Sistem Distribusi Tenaga Listrik 20 kV pada Penyulang CWRU - Tasma Sucita; Maman Somantri; Diki Fahrizal; Mia Agista (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
The electricity demand continues to rise alongside population growth, making the reliable distribution of electrical energy to consumers essential. The reliability of the 20 kV electricity distribution system on the CWRU feeder at the National Electricity Company (Perusahaan Listrik Negara, PT PLN) Customer Service Unit (Unit Layanan Pelanggan, ULP) Pelabuhan Ratu Area Surade was evaluated. The primary purpose was to analyze key reliability indices such as system average interruption frequency index (SAIFI), system average interruption duration index (SAIDI), customer average interruption duration index (CAIDI), average service availability index (ASAI), and average service unavailability index (ASUI), and to assess the economic impact of disruptions on consumers. Methodologies involved collecting and analyzing field data from PT PLN (Persero) ULP Pelabuhan Ratu’s CWRU feeder, utilizing quantitative reliability calculations and qualitative observations to identify internal and external factors affecting system reliability. The results showed that the SAIFI value reached 52.077 times/customer/year, and the SAIDI value was 99.400 hours/customer/year, classifying the system as unreliable based on PLN standards (standar PLN, SPLN) 68-2:1986. However, the CAIDI value of 1.813 hours/times/year indicated that the system response time was within acceptable limits. The availability of electricity, with an ASAI of 99.828% and an ASUI of 0.172%, was deemed satisfactory. Internal factors contributed to 10.47% disturbances. In contrast, external factors (weather and tree fall) accounted for 48.84%, and the remaining 40.69% were from unknown causes. Economic losses were calculated at Rp52,432.50/customer because these interruptions. More frequent maintenance and the implementation of additional protective measures are recommended to enhance reliability.